Ethanol and cannabinoids interact to alter behavior in a zebrafish fetal alcohol spectrum disorder model. Issue 12 (16th January 2019) - Boa‐Amponsem, Oswald; Zhang, Chengjin; Mukhopadhyay, Somnath; Ardrey, Iman; Cole, Gregory J.
Abstract : Background: Recent work suggests that endocannabinoids (eCBs) may signal through the sonic hedgehog signaling pathway. We therefore hypothesized that combined ethanol and eCB exposure during defined stages of zebrafish embryogenesis will produce deficits comparable to human fetal alcohol spectrum disorder (FASD). Methods: Zebrafish embryos were exposed to ethanol or cannabinoid agonists alone or in combination at defined developmental stages and assessed for changes in brain morphology or expression of marker genes such as p ax6a . Juvenile fish were then assessed for risk‐taking/anxiety‐like behavior using the novel tank dive test. Results: Either chronic or acute exposure to high doses of the CB1R agonist ACEA resulted in FASD phenotypes. However, acute subthreshold doses of CB1R agonist alone, or combined with 0.5% ethanol, did not induce morphological phenotypes, but did induce dysmorphogenesis when combined with acute 1% ethanol. Phenotypes were rescued using the CB1R antagonist SR141716A. In addition, JZL195, a dual inhibitor of FAAH and MAGL, two degradative enzymes for eCBs, induced FASD phenotypes in the presence of subthreshold ethanol, confirming the activation of common signaling pathways by ethanol and eCBs. We next analyzed the effects of ethanol and CB1R agonist on juvenile zebrafish behavior and show that ACEA or ethanol alone did not alter behavior, but combined ACEA and ethanol increased risk‐taking behavior. Conclusions: These studies demonstrate that pathological and behavioral phenotypes associated with FASD are induced by exposure to CB1R agonists and suggest that combined exposure to lower levels of alcohol and marijuana may be capable of inducing FASD‐like morphological and behavioral impairments.